(untitled) (European Journal of Pure and Applied Mathematics, 2010)
In this study, we have given a generalization of the iterative decreasing dimension method given in [1] and a generalization of the iterative decreasing dimension algorithm based on this method. The algorithm is suited for implementation using computer algebra systems such as Maple And Matlab. So we also have given symbolic and numerical examples using this algorithm and a Maple procedure for the algorithm.